A Retrospective Study on Side of Nerve Involvement and Distribution of Pain in Patients with Trigeminal Neuralgia (Indian Journal of Public Health Research & Development, 2020)
BACKGROUND: Trigeminal neuralgia is chronic, debilitating and painful condition involving the trigeminal nerve and has a major impact on patients’ quality of life. It is characterized by brief attacks of excruciating pain in the area of distribution of one or more branches of the trigeminal nerve. It has an annual incidence of about 4.5 to 12.6 per 100,000 population and has a female predilection. According to studies, it commonly occurs in the older age group and a hallmark of idiopathic trigeminal neuralgia is that it occurs twice as often on the right side of the face. There are various hypotheses proposed to explain this side predilection. AIM: To evaluate and analyze the side of occurrence, distribution of pain in patients diagnosed with trigeminal neuralgia among patients visiting Saveetha Dental College. MATERIALS AND METHOD: The retrospective clinical data of 42 patients who reported with a complaint of orofacial pain and diagnosed with trigeminal neuralgia in the department of Oral Medicine and Radiology, Saveetha Dental College from Jan 2016 to Dec 2017 were obtained. The data regarding age of onset, gender, side of nerve involvement, and distribution of pain was retrieved and analyzed. RESULTS: Trigeminal neuralgia was mostly diagnosed in the 5th and 6thdecades of life with a mean age of 55.3 years. Male patients were affected more than female patients but the difference was not comparable. It affected the right side more frequently and the maxillary branch was the most commonly involved. CONCLUSION: This study investigated the clinical characteristics of 42 patients diagnosed with trigeminal neuralgia. Further multicentre studies need to be done to investigate the clinical characteristics and imaging studies need to be done along with anatomical studies to investigate causes for nerve entrapment as an etiological agent for trigeminal neuralgia.
Keywords: Trigeminal neuralgia, site predilection, trigeminal nerve, orofacial pain, neuropathic pain